2012
DOI: 10.1590/s1516-35982012000300044
|View full text |Cite
|
Sign up to set email alerts
|

Production and quality of milk from Mantiqueira dairy cows feeding on Mombasa grass pasture and receiving different sources of roughage supplementation

Abstract: -Production and quality of milk from dairy cows grazing exclusively on Mombasa grass pasture, during the spring-summer period and fed roughage supplementations, during the autumn-winter, were evaluated in two consecutive years.The pasture of 11.4 ha was divided into 57 paddocks of 2,000 m 2 each, including three replications with 19 paddocks each.The pasture was managed with two occupation days and 36 resting days. During the spring-summer period, cows received only grass pasture. In the autumn-winter period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
3
6
1
Order By: Relevance
“…CP content of BKO at 135 and 150 g kg -1 DM for BKC cover the protein requirement for moderate and low yielding dairy cows. These are comparable to reports in the literature, although CP content may be up to 240 g kg -1 DM with high N fertilization (160 kg N ha -1 ) (Salgado et al, 2010;Peres et al, 2012;Restelatto et al, 2013;Sánchez-Gutiérrez et al, 2014). BKC herbage had a higher although nonsignificant (P > 0.05) content of CP, maybe due to the contribution of red clover in the grazed plot (4.8% DM).…”
Section: Black Oat and Pasture Variablessupporting
confidence: 86%
See 1 more Smart Citation
“…CP content of BKO at 135 and 150 g kg -1 DM for BKC cover the protein requirement for moderate and low yielding dairy cows. These are comparable to reports in the literature, although CP content may be up to 240 g kg -1 DM with high N fertilization (160 kg N ha -1 ) (Salgado et al, 2010;Peres et al, 2012;Restelatto et al, 2013;Sánchez-Gutiérrez et al, 2014). BKC herbage had a higher although nonsignificant (P > 0.05) content of CP, maybe due to the contribution of red clover in the grazed plot (4.8% DM).…”
Section: Black Oat and Pasture Variablessupporting
confidence: 86%
“…There are not many reports in the literature on black oat associated with legumes. NDF and ADF contents were similar to other work, although higher than reported by Salgado et al (2010) and Peres et al (2012). Prado et al (2003) from work on black oat reported a range between 405 and 694 g kg -1 DM, from 223 to 435 g kg -1 DM for ADF, and from 87.4 to 210 g kg -1 DM for CP.…”
Section: Black Oat and Pasture Variablessupporting
confidence: 85%
“…However, the low rate of fiber degradation in the rumen associated with pasture particle size and time spent ruminating possibly did not favor increased production of acetic acid in the rumen (Van Soest, 1994;Sousa et al, 2018;Santana et al, 2019ab). According to Peres et al (2012), milk fat content can also be altered by genetic variations, which did not occur in this research because animals belong to the same genetic group. For Lucci (1997), the dietary nitrogen source may influence milk fat content, so that increases in dietary protein concentration from 12% to 18% of DM reduces fat concentration by up to 5 g/kg milk due to increased milk yield.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the use of concentrate supplementation strategies was essential to correct foragelimiting nutrients and to ensure milk production in deferred pasture-based systems (mean of 11.50 kg/day). According to Peres et al (2012), the use of tropical forage plants is a low-cost strategy in dairy systems, allowing a more competitive operation. The authors also state that Holstein x Zebu crossbred cows on pasture have the potential to produce from 11.6 to 12.4 kg of milk/day without concentrate supplementation in the rainy season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation